BELAJAR MENGENAL KEBERAGAMAN BUDAYA INDONESIA DALAM PELAJARAN IPS DI SD - Fitri Yanti Muchtar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesia's broad cultural diversity covers various aspects of people's lives, such as ethnicity, language, customs and customs, which is both a challenge and an opportunity for education in Indonesia. At the elementary school (SD) level, introduction to cultural diversity is very important to build understanding and tolerance among students. However, in practice, teaching about Indonesian culture is often limited to certain aspects and is not comprehensive. This research aims to explore the importance of introducing Indonesian cultural diversity in Social Sciences (IPS) learning in elementary schools, as well as identifying effective methods in teaching this material. The methods used in this research are literature studies and studies of learning practices implemented in elementary schools. The research results show that learning methods that integrate folklore, introduction to traditional clothing, traditional music, and project-based learning can be effective in increasing students' understanding of cultural diversity. Apart from that, introducing culture can also foster a sense of love for the country, increase tolerance, and shape students' characters who are more respectful of differences